2018
DOI: 10.1186/s12889-018-5092-7
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce post-acute consequences of diarrheal disease in children: a systematic review

Abstract: BackgroundAlthough acute diarrhea often leads to acute dehydration and electrolyte imbalance, children with diarrhea also suffer long term morbidity, including recurrent or prolonged diarrhea, loss of weight, and linear growth faltering. They are also at increased risk of post-acute mortality. The objective of this systematic review was to identify interventions that address these longer term consequences of diarrhea.MethodsWe searched Medline for randomized controlled trials (RCTs) of interventions conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…While effective interventions exist for treating acute malnutrition (e.g., exclusive breastfeeding for the first 6 months of life, inpatient- and community-based management of acute malnutrition using corn-soy blend or ready-to-use therapeutic food; WHO, 2013 ; Bergeron and Castleman, 2012 ; Keats et al, 2021 ), there are few evidence-based guidance on how to reverse the effects of chronic malnutrition once a child is stunted ( Bergeron and Castleman, 2012 ; Leroy et al, 2015 ; Reinhardt and Fanzo, 2014 ; Pavlinac et al, 2018 ; WHO, 2015 ). We found that approximately one in five children experience severe growth faltering subsequent to acute diarrhea, that is, an additional ≥0.5 decrease in HAZ in the 2–3 months after acute diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…While effective interventions exist for treating acute malnutrition (e.g., exclusive breastfeeding for the first 6 months of life, inpatient- and community-based management of acute malnutrition using corn-soy blend or ready-to-use therapeutic food; WHO, 2013 ; Bergeron and Castleman, 2012 ; Keats et al, 2021 ), there are few evidence-based guidance on how to reverse the effects of chronic malnutrition once a child is stunted ( Bergeron and Castleman, 2012 ; Leroy et al, 2015 ; Reinhardt and Fanzo, 2014 ; Pavlinac et al, 2018 ; WHO, 2015 ). We found that approximately one in five children experience severe growth faltering subsequent to acute diarrhea, that is, an additional ≥0.5 decrease in HAZ in the 2–3 months after acute diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent findings on the association of oral rehydration therapy for diarrhea with outcomes may be because of the differential prevalence of children very close to the anthropometric failure cutoffs given that only they would be substantially affected by the occurrence of diarrhea and oral rehydration treatment. 49,50 The heterogeneous association between sanitation facility and child undernutrition may be attributed to differences in complementarity of toilet maintenance, including other water and hygiene practices. 51,52 Limitations There are several limitations to this study.…”
Section: Supplementary Analysesmentioning
confidence: 99%
“…However, it is unclear which groups of children are at highest risk. In addition, few interventions have been successful at mitigating the nutritional consequences of diarrhea [10]. Identifying risk factors for post-MSD linear growth faltering can inform which groups of children should be prioritized for inclusion in trials of potential interventions, and, once an effective intervention has been identified, to optimize the effectiveness of intervention delivery within programs by targeting children at high risk of growth faltering.…”
Section: Introductionmentioning
confidence: 99%